Como a felicidade no ambiente de trabalho influencia no objetivo da organização - Pissetti, Alessandra Maria Vasconcellos (2020)
Positive psychology enables the employees of a company to achieve high performance by feeling fulfilled, motivated, and committed to its goals. Although it was created more than 20 years ago, research in Brazilian on the subject is still scarce. It is important to know why the lack of happiness in the workplace influences the decrease in productivity. The aim of this paper is to present the concepts of positive psychology, the principles proposed in Shawn Achor’s The Happiness Advantage, and to correlate the main ideas with the applications documented in the literature and with the Brazilian labor market. Companies have been adapting to workers’ needs through periodic consultation on issues such as remuneration, training and managerial relations, adopting greater flexibility on work schedules and even opening up the possibility of working at home when possible. The pursuit of happiness in the workplace benefits both professionals, leading them not to succumb to everyday stress, and organizations that understand its importance.